Development and characteristics of stackable cassava (Manihot esculanta Crantz) chips - Ismail, Nur `Aini (2015)
The shortcoming of cassava chips products in the market which are; uneven shape and cannot be stacked have hindered the process of fitting cassava chips into cylindrical containers. These conditions have caused reduction in the attractiveness of the final product. In this study, the effects of process variables which are; the thickness and numbers of cassava slice, on the final shape of fried cassava chips were determined in order to develop cassava chips with stackable properties and acceptable quality as close as those displayed by fabricated potato chips. Moreover, the strength of cassava chips were evaluated through simulation test to imitate transportation and handling. A bigger frying setup was used to determine whether it could produce cassava chips with the intended stackable properties. Frying condition for mass production of cassava chips for SME industries was also studied. The shape of sliced cassava is ellipse with 5.0 cm major diameter and 4.8 cm minor diameters. Four different thickness measurements were used including 1.0 mm, 1.5 mm, 1.75 mm and 2.0 mm. Commercial potato chips with 1.27 mm thickness were used as control sample. Then, the sliced cassava was fried in the deep fat fryer with the temperature of 170℃ until no bubbles could be observed on the oil surface. For each thickness studied, different numbers of slices (10, 20, 30 and 40 slices) were fried simultaneously which resulted in different shapes of the fried cassava chips produced and the stacking ability of the chips was also recorded. The results show that there are 6 shapes of fried chips produced after frying in which curvy shape was chosen by the panelists as the best shape as it delivered the same characteristics as the control. High ratio of the numbers of cassava slices to frying area resulted in less curvy shape of the fried cassava chips due to the limited space between the sliced cassava. Cassava chips with thickness of 2.0 mm have higher strength and absorb less oil during frying compared to other thickness. To conclude, cassava chips thickness and numbers of slice during frying affect the final shape of cassava chips. Thirty cassava slices with the thickness of 2.0 mm yield the highest number of curvy shape when fried using frying temperature of 170℃, 594 cm2 of frying area and frying time of 120 seconds.